The organization of anticorruption: Getting incentives right! - Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2008)
Governments and private firms try to contain corruption among their staff mostly in a top-down, rules-based approach. They limit discretion, increase monitoring or impose harsher penalties. Principles-based, bottom-up approaches to anticorruption, instead, emphasize the importance of value systems and employee's intrinsic motivation. This embraces the invigorating of social control systems, encouraging whistle-blowing, coding of good practice and alerting to red flags. This paper investigates how some top-down measures run counter to bottom-up contributions. Examples range from penalties imposed with zero-tolerance, debarment or the nullity of contracts. While top-down elements are indispensable for containing corruption they must be designed well in order to avoid discouraging the bottom-up endeavors.
Keywords: D73; K42; 330; Corruption; whistle-blowing; contract penalties; debarment; nullity